The Effectiveness of Content Mastery Services Using the Approach Self Directed Learning to Increase Student Self Confidence - Wetnawati Wetnawati; Indah Sukmawati (Jurnal Neo Konseling, 2019)
Self-confidence is an attitude that students need to have in order to develop their potential optimally. But in reality at school students are still afraid to express opinions in front of the class, afraid of being laughed at by friends when expressing opinions in front of the class. Many things can be done to improve student            confidence one of them by utilizing guidance and counseling services, namely content mastery services. Thisstudy aims to examine differences in student confidence before and after content mastery services are provided using a self directed learning approach. This research uses quantitative methods. This type of research is a pre-experiment, using the one pretest-posttest design. The subjects of this study were 12 students of SMP Negeri 13 Padang in class VIII of 12 students. Data were analyzed using nonparametric statistical techniques using the Wilcoxon Signed Rank Test. The results of the study noticed that the pretest score was 1480 and posttest 1951. Furthermore for the Asymp hypothesis test. Sig. (2-tailed) students' confidence in the experimental group was 0.002 or the probability under alpha 0.05 (0.002 ≤ 0.05) of these results revealed that Ho was rejected and H1 was accepted. Based on the results of this study, it was concluded that content mastery services using an effective self directed learning approach to increase student confidence.